Proposed Marketing Strategy For Mokkara Indonesia - Purwita Sundari, Ita; Ashari Nasution, Reza (The Indonesian Journal of Business Administration, 2016)
Abstract. Fashion is one of important industry in developing of Indonesia Creative Industry. According to Creative Economy Corporation (BEKraf) reports that the development of Indonesia fashion in 2015 is the second biggest among creative businesses in Indonesia and also obtained from BPS Creative Industry Development around 16 creative economies reaching 63%. One of efforts from Creative Economy and Tourism Ministry is making go local programs bringing local wisdom in brand of Indonesia, prompting raw materials which is environmentally friendly and making cultural fashion such as Batik and Kebaya Mokkara Indonesia is a small industry. Mokkara. Indonesia produces traditional Indonesian clothing namely kebaya kutu baru as a newly established company, Mokkara facing business issues that the purchase amount is only 13% . This research attempts to formulate appropriate strategies for Mokkara to increase the number of purchases and the number of repeatpurchases Keywords : Marketing Strategy, Batik, Creative Industry